2014
DOI: 10.1097/coc.0b013e31827e4eb9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Image-guided Radiotherapy Technologies for Prostate Cancer

Abstract: Radiation oncology has seen a rapid increase in the use of image-guided radiotherapy technology (IGRT) for prostate cancer patients over the past decade. The increase in the use of IGRT is largely driven by the fact that these technologies have been approved by the Food and Drug Administration and are now readily reimbursed by many insurance companies. Prostate cancer patients undergoing intensity modulated radiotherapy (IMRT) now have access to a wide variety of IGRTs that can cost anywhere from $500,000 or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 38 publications
0
35
0
3
Order By: Relevance
“…The need for CMI, given the tight 3-mm posterior margin, is consistent with the findings of Mayyas et al (14), who reported that a posterior margin of 3.9 mm was needed to account for residual setup error and intrafractional motion. A study by Wu et al (3) and a review Das et al (15) also pointed out that the Calypso-based intervention would make possible the detection and correction of patients exhibiting occasional large shifts. This will be of much greater importance in hypofractionated treatment.…”
Section: Discussionmentioning
confidence: 95%
“…The need for CMI, given the tight 3-mm posterior margin, is consistent with the findings of Mayyas et al (14), who reported that a posterior margin of 3.9 mm was needed to account for residual setup error and intrafractional motion. A study by Wu et al (3) and a review Das et al (15) also pointed out that the Calypso-based intervention would make possible the detection and correction of patients exhibiting occasional large shifts. This will be of much greater importance in hypofractionated treatment.…”
Section: Discussionmentioning
confidence: 95%
“…[51][52][53][54][55] Our robustness settings assume that any systematic and random shift in the target position will be accounted for using daily online imaging and position correction; this would be reasonable for proton therapy given recent developments in IGRT. [56][57][58] Robustness settings would have no impact on the average dose agreement between heterogeneous sCT and CT. Different perturbation distances might shift the observed gamma pass rates for homogeneous sCT and dual bulk sCT relative to the (dotted) line of equivalence on Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In current radiotherapy practice, various methods of target localization are used to correct for prostate motion 6. Standard practice in Australia is to use radiographic imaging to visualize radiopaque fiducial markers implanted into the prostate 2, 7.…”
Section: Introductionmentioning
confidence: 99%